Time-resolving state-specific molecular dissociation with XUV broadband absorption spectroscopy - Magunia, Alexander; Rebholz, Marc; Appi, Elisa; Papadopoulou, Christina C.; Lindenblatt, Hannes; Trost, Florian; Meister, Severin; Ding, Thomas; Straub, Michael; Borisova, Gergana D.; Lee, Junhee; Jin, Rui; et al. (Science advances, 2023)
The electronic and nuclear dynamics inside molecules are essential for chemical reactions, where different pathways typically unfold on ultrafast timescales. Extreme ultraviolet (XUV) light pulses generated by free-electron lasers (FELs) allow atomic-site and electronic-state selectivity, triggering specific molecular dynamics while providing femtosecond resolution. Yet, time-resolved experiments are either blind to neutral fragments or limited by the spectral bandwidth of FEL pulses. Here, we combine a broadband XUV probe pulse from high-order harmonic generation with an FEL pump pulse to observe dissociation pathways leading to fragments in different quantum states. We temporally resolve the dissociation of a specific O2+ state into two competing channels by measuring the resonances of ionic and neutral fragments. This scheme can be applied to investigate convoluted dynamics in larger molecules relevant to diverse science fields.